1982
DOI: 10.1073/pnas.79.6.1849
|View full text |Cite
|
Sign up to set email alerts
|

Probing the energetics of proteins through structural perturbation: sites of regulatory energy in human hemoglobin.

Abstract: The sites of energy transduction within the human hemoglobin molecule for the regulation of oxygen affinity have been determined by an extensive study of the molecule's energetic response to structural alteration at individual amino acid residues. For 22 mutant and chemically modified hemoglobins we have determined the total free energy used by the tetrameric molecule for alteration ofoxygen affinity at the four binding steps. The results imply that the regulation of oxygen binding affinity is due to energy ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
39
0

Year Published

1984
1984
2012
2012

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(42 citation statements)
references
References 49 publications
3
39
0
Order By: Relevance
“…For both hemoglobins, the spectra of oxygen derivatives are invariant over the pH range in which the proteins are stable (pH 6 -9). Our spectral invariance confirms the lack of an enhanced dissociation into dimers in hemoglobin San Diego [16]. …”
Section: Absorptionsupporting
confidence: 69%
“…For both hemoglobins, the spectra of oxygen derivatives are invariant over the pH range in which the proteins are stable (pH 6 -9). Our spectral invariance confirms the lack of an enhanced dissociation into dimers in hemoglobin San Diego [16]. …”
Section: Absorptionsupporting
confidence: 69%
“…USA 82 (1985) V.Yj oxyhemoglobin (20), and human carboxyhemoglobin (21) are closely similar in regard to quaternary structure, although minor tertiary structure differences exist. (ii) The total cooperative free energy (over all four steps) differs by only a few tenths of a kcal/mol (out of -6) for these three ligands (9). (iii) The pattern of energetic effects we find for cyanomethemoglobin is supported by results of kinetic and spectral studies with the ligand NO (22,23) and by cryogenic isoelectric focusing studies with CO (24), all of which indicate species [21] and [22] to dominate the distribution of doubly ligated tetramers and to have different properties from the other members of this set.…”
Section: Discussionmentioning
confidence: 99%
“…In an extensive series of measurements of the rate constants for association of normal, mutant, and chemically modified hemoglobins over a wide range of pH, this value was found to be invariant (9,15). The value of kf used in this study was also found to be in good agreement with that calculated from the values of 4K21 and kr determined independently for cyanomet hemoglobin with all four subunits ligated.…”
mentioning
confidence: 99%
“…refs. [6][7][8][9][10][11][12][13][14][15]. These studies, and work from other laboratories, have resulted in findings that impose stringent constraints on the nature of interactions responsible for cooperativity.…”
mentioning
confidence: 95%
“…In the past, the structural analyses have provided an admirable wealth of detailed (atomic-level) information, whereas the corresponding development of energetic information has been severely lagging. Thus models based upon detailed structural assumptions-e.g., the Perutz mechanism (21, 22)-have only recently become amenable to critical tests (3)(4)(5)(12)(13)(14). An example is the detailed model of Szabo and Karplus (23), which we have now tested against the extensive sets of highly accurate pH-dependent oxygenation data recently obtained (15).…”
mentioning
confidence: 99%